Effects of fabrication method on initial powder characteristics and liquid phase sintering behaviour of tungsten - Erol, Mahmut; Erdogan, Metehan; Karakaya, Ishak (ELSEVIER SCI LTD, 2018)
Direct electrochemical production of tungsten involves removal of oxygen in solid state from an important tungsten compound, calcium tungstate, in molten salts. A detailed experimental study was performed to characterize the liquid phase sintering behaviour of the tungsten powder (WE), which was produced by the direct electrochemical reduction technique. All of the tungsten heavy alloy (WHA) compositions covered in this study, contained four parts nickel, one part cobalt and over 90 wt% tungsten. The pellets were sintered at 1500 and 1550 degrees C under continuous flow of an equimolar hydrogen-argon gas mixture. A commercially available tungsten powder (W-C) was also used to prepare the same tungsten heavy alloy compositions as those prepared by the electrochemically produced tungsten powder to act as a control group. Scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray fluorescence (XRF) and hardness measurements were employed for characterization. The analyses provided that; the tungsten powder as obtained from the direct electrochemical reduction process contained some unreduced CaWO4 particles and they limited the grain growth and mass transport in the liquid phase. Although calculated relative densities were a bit lower than desired, the tungsten heavy alloys produced by the electrochemical reduction technique was promising for use when average grain size, dissolved tungsten contents and general/matrix hardness values are considered.
Keywords: Electrochemical reduction; Tungsten production; Liquid phase sintering; Tungsten heavy alloys; HEAVY ALLOYS; MECHANICAL-PROPERTIES; MICROSTRUCTURAL PARAMETERS; MOLTEN-SALT; FE; SEGREGATION; COMPOSITES; CAWO4; OXIDE; Materials Science; Metallurgy & Metallurgical Engineering